Evaluation of non-invasive hemoglobin measurement in blood donors at a tertiary care hospital, Bangkok, Thailand - Ratinan Dangwilailert; Somboon Lekmak; Duangtida Promlee; Tanyaporn Pongkunakorn; Parichart Permpikul (PLoS ONE, 2026)
Background Hemoglobin (Hb) assessment is crucial to prevent blood donation from anemic donors. Most measurements are invasive and painful; however, an alternative, non-invasive hemoglobin measurement is available. This study aimed to compare non-invasive and point-of-care invasive hemoglobin test results with those from an automated blood analyzer in blood donors. Methods Qualified blood donors were enrolled at a tertiary care hospital in Bangkok, Thailand. Hemoglobin was initially measured by the non-invasive device (Rad-67 Pulse CO-Oximeter) and a point-of-care invasive hemoglobin screening device (Mission HemoPro). Participants with point-of-care invasive hemoglobin ≥ 12.5 g/dL were eligible to donate, and during donation, standard hemoglobin measurements were obtained using an automated analyzer, XN-550. Those who were ineligible with point-of-care invasive hemoglobin < 12.5 g/dL underwent additional blood sampling for hemoglobin measurement by an automated analyzer. Correlation and agreement between non-invasive, point-of-care, and automated hemoglobin measurements were assessed with Intraclass Correlation Coefficient (ICC) and Bland-Altman plots, while satisfaction was evaluated using a Likert scale. Results Of 300 participants, 295 had complete data. Of these, 169 were male (57.28%). Average non-invasive, point-of-care, and automated hemoglobin levels were 14.38 ± 1.12 g/dL, 13.65 ± 0.70 g/dL, and 13.90 ± 1.16 g/dL, respectively. The ICC between non-invasive, point-of-care, and automated hemoglobin measurement was 0.600 (95% CI: 0.522–0.668) and 0.897 (95% CI: 0.872–0.957). The sensitivity of the non-invasive Hb measurement was poor for detecting anemic donors when the Hb cut-off was set at 12.5 g/dL. This method received significantly higher satisfaction than the routinely used invasive device. Conclusion The non-invasive Hb measurement in blood donors showed moderate agreement with the standard test, but the sensitivity was poor when the cut-off hemoglobin was set at 12.5 g/dl. Since donor satisfaction was higher, this method may be used as an alternative screening tool, provided a higher Hb cut-off value is used.